2021
DOI: 10.3389/fcell.2021.697614
|View full text |Cite
|
Sign up to set email alerts
|

A KDM4-DBC1-SIRT1 Axis Contributes to TGF-b Induced Mesenchymal Transition of Intestinal Epithelial Cells

Abstract: Intestinal fibrosis is one of the common pathophysiological processes in inflammatory bowel diseases (IBDs). Previously it has been demonstrated that epithelial-mesenchymal transition (EMT) can contribute to the development of intestinal fibrosis. Here we report that conditional ablation of SIRT1, a class III lysine deacetylase, in intestinal epithelial cells exacerbated 2, 4, 6-trinitro-benzene sulfonic acid (TNBS) induced intestinal fibrosis in mice. SIRT1 activity, but not SIRT1 expression, was down-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 88 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…It has been reported that DBC1 cooperates with SIRT1 to mediate different physiological functions within mammalian cells. For example, stimulation of DBC1 transcription inhibits SIRT1 activity, contributing to TGF-β-induced epithelial–mesenchymal transition ( Chen et al, 2021 ). Additionally, SIRT7 represses DBC1 transcription to promote thyroid tumorigenesis by binding to the promoter of DBC1 ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DBC1 cooperates with SIRT1 to mediate different physiological functions within mammalian cells. For example, stimulation of DBC1 transcription inhibits SIRT1 activity, contributing to TGF-β-induced epithelial–mesenchymal transition ( Chen et al, 2021 ). Additionally, SIRT7 represses DBC1 transcription to promote thyroid tumorigenesis by binding to the promoter of DBC1 ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-cell lysates were obtained by resuspending cell pellets in radioimmunoprecipitation assay (RIPA) buffer (50 mM Tris pH7.4, 150 mM NaCl, 1% Triton X-100) with freshly added protease inhibitor (Roche, Basel, Switzerland) as previously described. 29 Typically, 100 μl RIPA buffer was used for 1 × 10 6 cells. Moreover, 30 μg of protein was loaded in each lane and separated by 8% SDS-PAGE gel with all-blue protein markers (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Transient transfections were performed with Lipofectamine LTX (for DNA plasmid) or Lipofectamine RNAiMax (For siRNA) per vendor recommendation. Luciferase activities were assayed 24-48 hours after transfection using a luciferase reporter assay system (Promega) as previously described [ 56 58 ].…”
Section: Methodsmentioning
confidence: 99%